PENGARUH SPA BAYI TERHADAP PENINGKATAN BERAT BADAN BAYI USIA 4-6 BULAN DI WILAYAH KERJA PUSKESMAS TAPIAN DOLOK KABUPATEN SIMALUNGUN - Parmiana Bangun (Poltekkes Kemenkes Medan, 2021)
Infan is the period as well as the time of Christ's development. It is said to be a critical period because this period is very short for the environment and it is said to be a development period because infancy is not very short and can be repeated again. The most important period of child development is infancy and toddlerhood. In infancy / toddler there is a basic growth that will determine the next child's development. Infancy is the first month of life, the baby will adapt to the environment, changes in blood circulation, and begin to work the organs of the body, and in post-neonatal the baby will experience very fast growth. One way to stimulate growth and development in children is to use the baby solus per aqua (SPA) technique. Babies who are given SPA Babies will certainly grow and develop differently from the growth and development of babies who are not given SPA Babies. This is because the Baby SPA series aims to awaken the baby's sensory and motor nerves early with certain stimuli so that babies can grow actively and be more optimal both physically and mentally. This study aims to obtain an overview of the effect of Infant SPA on weight gain aged 4 to 6 months, Measuring the weight gain of infants aged 4 to 6 months who receive and Infant SPA and those who do not receive massage and Infant SPA at the Tapian Dolok Health Center, Simalungun Regency. The hypothesis in this study is that the increase in the weight of the babies who received the Baby Spa was greater than the standard deviation of the weight gain of 36.9 with a mean difference of 48.7 grams between the two groups. The sample size obtained is 12 respondents so that the number of samples will be increased to 30 according to the minimum sample that can be analyzed statistically. So the intervention group was 30 babies and the control group was 30 babies. The results showed that there was an effect of SPA for infants on weight gain of infants at the age of 4 to 6 months. This study is expected to provide knowledge to mothers who have babies aged 4 6 months the importance of SPA for babies to the baby's weight gain.